Diagnostic accuracy of magnetic resonance imaging techniques for treatment response evaluation in patients with head and neck tumors, a systematic review and meta-analysis. - Anouk van der Hoorn; Peter Jan van Laar; Gea A Holtman; Henriette E Westerlaan (PLoS ONE)
Background Novel advanced MRI techniques are investigated in patients treated for head and neck tumors as conventional anatomical MRI is unreliable to differentiate tumor from treatment related imaging changes. Purpose As the diagnostic accuracy of MRI techniques to detect tumor residual or recurrence during or after treatment is variable reported in the literature, we performed a systematic meta-analysis. Data sources Pubmed, EMBASE and Web of Science were searched from their first record to September 23th 2014. Study selection Studies reporting diagnostic accuracy of anatomical, ADC, perfusion or spectroscopy to identify tumor response confirmed by histology or follow-up in treated patients for head and neck tumors were selected by two authors independently. Data analysis Two authors independently performed data extraction including true positives, false positives, true negatives, false negatives and general study characteristics. Meta-analysis was performed using bivariate random effect models when ≥5 studies per test were included. Data synthesis We identified 16 relevant studies with anatomical MRI and ADC. No perfusion or spectroscopy studies were identified. Pooled analysis of anatomical MRI of the primary site (11 studies, N = 854) displayed a sensitivity of 84% (95%CI 72-92) and specificity of 82% (71-89). ADC of the primary site (6 studies, N = 287) showed a pooled sensitivity of 89% (74-96) and specificity of 86% (69-94). Limitations Main limitation are the low, but comparable quality of the included studies and the variability between the studies. Conclusions The higher diagnostic accuracy of ADC values over anatomical MRI for the primary tumor location emphases the relevance to include DWI with ADC for response evaluation of treated head and neck tumor patients.